2020
DOI: 10.31348/2020/30
|View full text |Cite
|
Sign up to set email alerts
|

Presbyopia Management with Diffractive Phakic Posterior Chamber IOL

Abstract: Objective: To evaluate safety and refractive efficiency after posterior chamber diffractive implantable phakic contact lens (IPCL) surgery. Material and Methods: A prospective non-randomized case-series study was performed on 54 myopic eyes of 27 patients who had undergone diffractive IPCL surgery. Corneal endothelial cell density (ECD), central corneal thickness (CCT), intra-ocular pressure (IOP), vault, uncorrected distance (UDVA), spherical equivalent (SE) and defocus curve, were all evaluated twelve months… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…IOP then returned to near preoperative values for the rest of the follow-up period. This was concomitant with other studies such as Bianchi et al [ 14 , 15 ]. AS-OCT was used for angle evaluation with ICL as in the study by Singh et al who implanted ICL in 32 eyes and found stable angle narrowing over 3 months of follow-up as well as Gargallo-Martinez who studied the ICL vault using AS-OCT.…”
Section: Discussionsupporting
confidence: 91%
“…IOP then returned to near preoperative values for the rest of the follow-up period. This was concomitant with other studies such as Bianchi et al [ 14 , 15 ]. AS-OCT was used for angle evaluation with ICL as in the study by Singh et al who implanted ICL in 32 eyes and found stable angle narrowing over 3 months of follow-up as well as Gargallo-Martinez who studied the ICL vault using AS-OCT.…”
Section: Discussionsupporting
confidence: 91%
“…In this model, the diffractive optical zone is 5.8 mm and is available in near additions between +1.50 and +4.00 D. The lens sizes available are between 11 and 14 mm in steps of 0.25 mm [48]. Bianchi performed at prospective nonrandomised case-series study using the IPCL lens for presbyopia [49]. Fifty-four eyes of 27 myopic patients were included.…”
Section: Presbyopia Correctionmentioning
confidence: 99%
“…In order to help people with presbyopia, many options are being developed besides spectacles, including pharmacological treatments, corneal procedures, phakic and pseudophakic intraocular lenses (IOL) with different optical designs and therapeutic combinations, trying to achieve the best visual performance for all distances. [ 6 7 8 9 10 11 12 13 14 15 ]…”
mentioning
confidence: 99%